The possible genetic influence on the susceptibility of exotic, Fulani, and Yoruba ecotype indigenous chickens to experimental Salmonella enteritidis (2012)
This study was conducted to evaluate the possible genetic resistance of exotic and indigenous chicks to Salmonella enteritidis. A total of 72 9 weeks old chicks were for this study which include the Fulani ecotype (FSF), Yoruba ecotype (YSF), and the Exotic breed (Black Nera cockerel). Chicks were infected with 3.8 x104 CFU of S. enteritidis and were observed for 16 days. Evaluation of possible genetic resistance was based on clinical signs, mortality and differential leukocytes count of infected chicks. Clinical signs were evident on day 3 with eighty three percent (83.3%) of the chicks showing severe clinical signs on day 8 post infection. The exotic breed had the most prolonged clinical signs with all the chicks showing severe clinical signs. Yoruba ecotype had the shortest timing for the clinical signs, with 62.5% of the Yoruba ecotype affected. 87.5% of the Fulani ecotype and 98% of the exotic breed were affected. No mortality was recorded with the chicks infected with S. enteritidis. Assessing the clinical signs observed from infected chicks revealed that Yoruba ecotype is the least susceptible. The result from the study also indicated that the exotic is more susceptible to Salmonella infection than the indigenous chicks. It also revealed that within the ecotypes in Nigeria, Fulani ecotype is more susceptible to Salmonella infection than the Yoruba ecotype. The differential susceptibility and the low mortality observed in Yoruba ecotype indicated probable genetic resistance to S. enteritidis